2010
DOI: 10.1002/jsfa.4108
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and nutritional quality of sea cucumbers

Abstract: Sea cucumbers are a seafood with high protein and low fat levels. The amino acid contents were similar but fatty acid profiles were different among species. The comparison showed that T. ananas, A. mauritiana and B. argus possessed higher nutritional values than other sea cucumber species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
204
4
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(264 citation statements)
references
References 26 publications
45
204
4
11
Order By: Relevance
“…The present result agrees with that of Wen et al (2010) who showed that glycine was abundant in Stichopus herrmanni, Thelenota ananas, Thelenota anax, Holothuria fuscogilva, Holothuria fuscopunctata, Actinopyga caerulea and Bohadschia argus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present result agrees with that of Wen et al (2010) who showed that glycine was abundant in Stichopus herrmanni, Thelenota ananas, Thelenota anax, Holothuria fuscogilva, Holothuria fuscopunctata, Actinopyga caerulea and Bohadschia argus.…”
Section: Discussionsupporting
confidence: 93%
“…Among the investigated sea cucumbers Actinopyga mauritiana showed the highest value of protein and lowest value of ash. This result is in accordance with the study of Wen et al (2010) The present study showed that the non essential amino acid glycine is dominant in all investigated sea cucumbers. It has been known that glycine is used to help create muscle tissue and convert glucose into energy.…”
Section: Discussionsupporting
confidence: 93%
“…Carbohydrate content by difference, soxhlet method fat content, ash content methods [7], and water content [7], spectrophotometric (At ug/l).…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Sea cucumbers and their extracts have been well documented for their strong effectiveness against hypertension, asthma, rheumatism, cuts and burns, impotence and constipation [51][52][53][54][55][56]. Nutritionally, sea cucumbers have an impressive profile of valuable nutrients such as Vitamin A, Vitamin B1 (thiamine), Vitamin B2 (riboflavin), Vitamin B3 (niacin), and minerals, especially calcium, magnesium, iron and zinc [57].…”
Section: Status Culture Application Management and Extinction Risksmentioning
confidence: 99%